OCTA and Doppler Ultrasound in Primary Open-Angle Glaucoma and Normal-Tension Glaucoma - Lestak, Jan; Fus, Martin; Rybář, Marain; Benda, Antonin (Life (Basel, Switzerland), 2023)
The aim of this study was to determine whether the values of vessel density (VD) and perfusion parameters in the ophthalmic artery (OA) and central retinal artery (CRA) of the same eye differ in patients with hypertensive glaucoma (HTG) from patients with normotensive glaucoma (NTG). The first group consisted of 20 HTG patients (40 eyes). Patients with HTG were verified to have primary open-angle glaucoma (POAG). The second group consisted of 20 HTG patients (40 eyes). VD was used to determine the Avanti RTVue XR from Optovue (USA). Peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistance index (RI) were measured in both the central retinal artery (CRA) and ophthalmic artery (OA) using Doppler sonography on the Affinity 70G from Philips (USA). The visual field (VF) was examined by a fast threshold glaucoma program using a Medmont M700 (Australia). We showed no differences in VF, VD, PSV-OA and EDV-CRA between the two groups. Statistically significant differences between the two groups were observed in PSV in CRA (p = 0.04), EDV in OA (p = 0.009) and in RI in both CRA and OA. Other values were without significant differences in both groups. In both HTG and NTG, we observed in PSV-CRA, EDV-OA, RI-CRA and RI-OA.
Keywords: primary open-angle glaucoma; normal-tension glaucoma; visual field; vessel density; color Doppler imaging (CDI)